Effect of various commercial of Na2SiO3 on compressive strength of Fly ash-based alkaline activated mortar. Issue 1 (May 2020) - Elbasir, Otman M. M.; Mijarsh, M.J.A.; Azmi Megat Johari, Megat; Mashri, Mohamed O. M.; Karolina, Rahmi; Arifin Ahmad, Zainal
Abstract: This study aimed to assesses the effect of various commercial Na2 SiO3 on the compressive strength (CS) of alkaline activated fly ash mortar (AAFM). The three mixture of alkaline activated mortar (AAM) C1, C2 and C3 were prepared from the source material of fly ash and alkaline activator solution (AAS). The initial AAS was comprised of NaOH (10M) and various grade of Na2 SiO3 . The various grades of Na2SiO3 were characterized by their SiO2 /Na2 O molar ratio of 2.0, 2.2, and 3.3, respectively. The sample from each mixture was characterized based on the CS and microstructure changes using useful tools of XRD and FTIR analysis. The results obtained indicated that the highest CS achieved among the three mixtures were 48.23MPa of mixture C2 prepared with SiO2 /Na2 O molar ratio of 2.2. This was mainly due to higher binder formation (N-A-S-H gel type) and a higher rate of reaction of the main source material. This result is in line with XRD and FTIR analysis results finding.